Wave manipulation in topological classical-wave systems - Yu, Letian (Nanyang Technological University, 2021)
For the past two decades, topological insulators have attracted extensive attention from both experimetal and theoretical physicists. These materials, which are insulating in the bulk and conducting at the interfaces of different domains, have been proven to support dissipation-less transport of electrons along their boundaries. This unique property has motivated explorations of similiar phenomena and led to successful discoveries of many novel toplogical states in classical systems. In this thesis, I investigate two scenarios in which topological insulators in classical systems exhibit novel properties, that are both new and promising for applications. Speci cally, through theoretical calculations and numerical simulations, I have observed broadband slow light in topological photonic crystals and antichiral edge states in acoustic systems.